Anti-inflammatory activity of 2-(5-((theophylline-7'-yl)methyl)-4-R-4H-1,2,4-triazole-3-ylthio)acetic acid salts - A. S. Gotsulya; Ye. S. Pruglo; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2014)
Inflammatory process is the leading pathogenic link of many diseases, which constitute about 80% of all pathologies in medical practice of any physician profession. Currently in a complex therapy of acute and chronic diseases a large number of drugs mainly from the group of non-steroidal anti-inflammatory drugs (NSAIDs) and glucocorticosteroids areusedas analgesics and anti-inflammatory preparations. NSAIDs is a group of substances with different structure (although, most of them are related to organic acids) with the overall therapeutic and adverse effects. The NSAID prototype is aspirin, so sometimes such drugs are called as similar to aspirin drugs. Most currently usedNSAIDs, inhibit cyclooxygenase-1 (constitutive iso-ferment) and cyclooxygenase-2 (isoferment, induced during the inflammation), disrupting the synthesis of prostaglandins and thromboxanes. The aim of this work was the valuation of anti-inflammatory activity of the 2-(5-((theophylline-7'-yl)methyl)-4-R-4Н-1,2,4-triazole-3-ylthio)-аcetic acidsalts on the model of acute inflammation "formalin-induced edema of the extremities" on rats and establishing the dependenceof pharmacological activityfrom structure. The objects of our research were 14 new compounds, namely salts of 2-(5-((theophylline-7'-yl)-methyl)-4-phenyl-4Н-1,2,4-triazole-3-ylthio)аcetic acid that have been synthesized at the Department ofToxicological and Inorganic Chemistry, of Zaporizhzhia state medical university. These compounds are crystalline substances, unscented, soluble in water or organic solvents. In accordance with the research results it has been found that 2-(5-((theophylline -7'-yl)methyl)-4-R-4Н-1,2,4-triazolo-3-ylthio)acetic acid and its diethylethanol-ammonium salt, by the strength of anti-inflammatory action exceeds the standard of comparison, namely diclofenac,both during 2 hours (at 26,63% and 42,15% respectively, p ˂ 0,01) and during 4 hours (at 1,79% and 6,96% respectively, p ˂ 0,05). Piperidine 2-(5-((theophylline-7'-yl)methyl)-4-phenyl-4Н-1,2,4-triazole-3-ylthio)acetateshould also be noted among the studied substances, as it shows high anti-inflammatory effect, the power of which is close to the action of sodium diclofenac (less active on 6,68%, p ˂ 0,05).